NOVASI ALAT PERMAINAN EDUKATIF DARI BARANG BEKAS UNTUK MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA DINI - Alwani, Kurratul (UNISAN JURNAL, 2025)
This study aims to determine the extent to which innovative educational play tools made from recycled materials can enhance early childhood language skills. Educational toys from recycled items offer a creative and eco-friendly alternative that can stimulate optimal language development in young children. The study employed a qualitative approach using observation, interviews, and documentation techniques conducted at an early childhood education center. The results showed that using educational tools from recycled materials increased children’s enthusiasm for learning, enriched their vocabulary, improved speaking abilities, and enhanced listening and comprehension skills. The interaction during play also built children’s confidence in communicating with peers and teachers. This innovation further encouraged educators to be more creative in developing learning aids from accessible local materials. Therefore, educational play tools made from recycled materials are appropriate alternative media to support the holistic language development of early childhood learners.